Religious Revival and Deprivatization in Post-Soviet Georgia Reculturation of Orthodox Christianity and Deculturation of Islam - Köksal, Pinar; Aydıngün, Ayşegül; Gürsoy, Hazar Ege (2019)
The countries of the former Soviet Union witnessed a religious revivalism in the final years of the regime, although following the collapse, the revivals of the different faith communities have had different characteristics. This article discusses the nature of the desecularization and deprivatization processes of both the Orthodox Christian Georgians and the Muslim minorities in Georgia. Based on field researches and indepth interviews conducted with elites and experts, it is argued that the revival of Orthodox Christianity in Georgia differs from the revival of Islam. While the Islamic revival has taken the form of a deculturation, very much in line with global processes, the Orthodox Christian revival is taking the form of a reculturation.